1999
DOI: 10.1002/(sici)1098-240x(199908)22:4<295::aid-nur4>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Test of the Fishbein and Ajzen models as predictors of health care workers' glove use

Abstract: The aim of this study was to identify predictors of health care workers' glove use when there is a potential for blood exposure. The study hypothesis was that an extension of the theory of planned behavior would explain more of the variance in glove use behavior than the theory of reasoned action or theory of planned behavior. A random sample of nurses and laboratory workers (N = 527) completed a 26-item questionnaire with acceptable content validity and reliability estimates. Using structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 30 publications
4
22
1
Order By: Relevance
“…Other clinicians included pharmacists [85,88,90,94], dentists [83,95], mental health professionals [86,87], psychologists [35], social workers [91], and a mix of different professions [84,89,92,93]. Among studies of physicians' intention, the prediction of intention related to clinical practice ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Other clinicians included pharmacists [85,88,90,94], dentists [83,95], mental health professionals [86,87], psychologists [35], social workers [91], and a mix of different professions [84,89,92,93]. Among studies of physicians' intention, the prediction of intention related to clinical practice ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include smoking cessation [25], condom use [26], healthcare worker glove use [27], and nurses’ pain management behaviour [28]. The TPB has also been suggested as a framework for assessing and teaching professionalism [29, 30].…”
Section: Diagnosing Ownership Problemsmentioning
confidence: 99%
“…Both the TRA and TPB have been useful in predicting various adherence intentions and behaviours including exercise programmes (Norman & Smith, 1995); antimalarial prophylaxis (Abraham et al, 1999); antihypertensive medication (Miller et al, 1992); and blood donation (Amponsah et al, 2000). Levin (1999) investigated whether the TRA or TPB could predict self-report glove use in health care workers. They found that the TRA was the most parsimonious predictor, explaining 70% of self-report glove use; although a study investigating physicians' intentions to wear gloves found that all three TPB constructs, including perceived behavioural control, were the most important predictors of intention to wear gloves (Godin et al, 1998).…”
mentioning
confidence: 99%